Liberal political perfectionism as a morally permissible, politically possible, and probably effective non-ideal theory - Araújo, Ricardo; Maurício Junior, Alceu (Sofia, 2026)
This article analyzes the position of the liberal political perfectionist proposal, understood as the state promotion of liberal political virtues, in relation to its practical necessity and feasibility. Initially, the authors present their proposal for liberal political perfectionism, emphasizing its fundamental practical importance for the maintenance and flourishing of liberal democracies. Then, in light of the current debate between ideal theories, non-ideal theories, and political realism, this article shows how such perfectionism, although based on markedly realist descriptions, should be considered a non-ideal theory due to its prior commitment to the normativity of egalitarian political liberalism, yet remaining capable of guiding political action. Finally, it argues that this commitment to the normativity of egalitarian political liberalism and the consequent departure from political realism do not lessen its effective applicability in liberal democratic societies.
Keywords: liberal political perfectionism; ideal theory; non-ideal theory; political realism; practical feasibility